Optimization of Islamic Daily Life Activity in Building Student’s Religious Character - Meilani, Lusi; Rena, Syahidah (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2025)
This study aims to examine the implementation of Islamic Daily Life Activities (IDLA) in shaping the religious character of students at SMP Bakti Mulya 400 Jakarta Selatan. Using a qualitative descriptive approach, data were gathered through observations, interviews with key school figures, and document analysis to understand IDLA’s implementation and effectiveness of the IDLA. The findings show that IDLA successfully instills religious values through regular activities, such as Dhuha prayer, congregational prayers, modest dress on Fridays, and charity initiatives, which collectively promote a consistent commitment to Islamic values, social responsibility, and spiritual fulfillment among students. This study concludes that the IDLA provides a viable model for religious character education, with implications for similar implementations in other Islamic educational settings and future research on its long-term effects beyond school.